ADVANTAGES OF USING APPLICATION SOFTWARE PACKAGES IN TEACHING THE CHAPTER OF MECHANICAL WAVES IN GENERAL SECONDARY SCHOOLS - Dehqonova, Ohista; Togonboyeva, Zeboxon (Физико-технологического образование, 2022)
this article describes the development based on practical software packages for teaching the Mechanical waves chapter in the 10th grade physics curriculum of general secondary schools.